The Cross Section of Expected Stock Returns: Nepalese Evidence - K.C., Indra Dhoj (PYC Nepal Journal of Management, 2024)
This study examines the impact of size, book-to-market equity ratio, cash flow yield, and earnings yield on the average stock returns of sample firms in Nepal. The analysis is based on the Fama and MacBeth (1973) model applied to pooled cross-sectional data from 51 NEPSE-listed companies. It includes 292 restricted observations spanning the period from 2010/11 to 2021/22, along with an assessment of portfolio properties. The findings reveal that results from developed economies do not fully align with those observed in least-developed economies like Nepal. For instance, the strong and statistically significant negative relationship between stock returns and the B/M ratio contradicts the positive association found in developed markets but aligns with previous studies in the Nepalese context. This study concludes that financial fundamentals do not entirely drive stock returns in Nepal’s capital market. The findings offer valuable insights for investors, policymakers, and other stakeholders.